The Ringworld engineers - Niven, Larry (Niven, Larry. Ringworld series., 1980)
Sequel to: Ringworld. Twenty years after discovering Ringworld, Louis Wu returns, the captive of a non-human race. To survive on the planet, which is no longer stable, he must locate the control center of the engineers who built the planet.